Tobacco use in Bollywood movies, tobacco promotional activities and their association with tobacco use among Indian adolescents. Issue 5 (5th July 2011) - Arora, Monika; Mathur, Neha; Gupta, Vinay K; Nazar, Gaurang P; Reddy, K Srinath; Sargent, James D
Abstract : Background: Smoking in Hollywood movies is a known risk factor for teen smoking in the USA and Europe, but little is known about the association between exposure to tobacco use in Bollywood movies and teen tobacco use in India. Methods: A cross-sectional sample of 3956 adolescents (eighth and ninth grades, ages 12–16 years) from 12 randomly selected New Delhi schools was surveyed in 2009, assessing tobacco use status, receptivity to tobacco promotions (based on owning or being willing to wear tobacco-branded merchandise) and exposure to tobacco use in movies. Quartiles of exposure to tobacco use in popular Bollywood movies released from 2006 to 2008 (n=59) were determined by content coding them for tobacco use and querying the adolescents whether they had seen each one. Logistic regression was used to control for covariates including age, gender, parent education, school performance, sensation-seeking propensity, family and peer tobacco use, and authoritative parenting. Results: Altogether, the 59 movies contained 412 tobacco use occurrences. The prevalence of ever tobacco use among adolescents was 5.3%. Compared with low-exposure adolescents (quartile 1), the adjusted odds of ever tobacco use among high-exposure adolescents (quartile 4) was 2.3 (95% CI 1.3 to 3.9). Being receptive to tobacco promotions was also associated with higher adjusted odds of ever tobacco use, 2.0 (95% CI 1.4 to 3.0). Conclusion: Watching tobacco use in Bollywood movies and receptivity to tobacco promotional activities were both independently associated with ever tobacco use among adolescents in India, with ORs being similar to the studies of adolescents elsewhere.